Novel nanocarrier of miconazole based on chitosan-coated iron oxide nanoparticles as a nanotherapy to fight Candida biofilms - Arias, Laís Salomão [UNESP] (2020)
Overexposure of microorganisms to conventional drugs has led to resistant species that require new treatment strategies. This study prepared and characterized a nanocarrier of miconazole (MCZ) based on iron oxide nanoparticles (IONPs) functionalized with chitosan (CS), and tested its antifungal activity against biofilms of Candida albicans and Candida glabrata. IONPs-CS-MCZ nanocarrier was prepared by loading MCZ on CS-covered IONPs and characterized by physicochemical methods. Minimum inhibitory concentration (MIC) of the nanocarrier was determined by the microdilution method. Biofilms were developed (48 h) in microtiter plates and treated with MCZ-carrying nanocarrier at 31.2 and 78 μg/mL, in both the presence and absence of an external magnetic field (EMF). Biofilms were evaluated by total biomass, metabolic activity, cultivable cells (CFU), extracellular matrix components, scanning electron microscopy and confocal microscopy. Data were analyzed by two-way ANOVA and Holm-Sidak test (p < 0.05). A nanocarrier with diameter lower than 50 nm was obtained, presenting MIC values lower than those found for MCZ, and showing synergism for C. albicans and indifference for C. glabrata (fractional inhibitory concentration indexes of <0.12 and <0.53, respectively). IONPs-CS-MCZ did not affect total biomass and extracellular matrix. IONPs-CS-MCZ containing 78 μg/mL MCZ showed a superior antibiofilm effect to MCZ in reducing CFU and metabolism for single biofilms of C. albicans and dual-species biofilms. The EMF did not improve the nanocarrier effects. Microscopy confirmed the antibiofilm effect of the nanocarrier. In conclusion, IONPs-CS-MCZ was more effective than MCZ mainly against C. albicans planktonic cells and number of CFU and metabolism of the biofilms.